POLA PERILAKU MASYARAKAT (KONSUMEN) DI KECAMATAN BATANGHARI LAMPUNG TIMUR DALAM MEMENUHI KEBUTUHAN DAN KEINGINAN HIDUP DAN DAMPAKNYA PADA PERUBAHAN KONFIGURASI KEBUTUHAN - Zumaroh, Zumaroh (JURNAL TAPIS, 2015)
Â ABSTRACTThis paper seeks to explain the behavior patterns of society (consumers) in the district of Batang East Lampung in meeting the needs and desires of his life and impact the behavior of people (consumers) in meeting the needs and desires of the configuration changes needed. This research is a descriptive field research. The location of this research is in the district of Batang East Lampung. Data were collected through documentation, questionnaire, and observation. The results showed that in the district of Batang Consumer behavior is influenced by the following factors: the level of education (learning experience), taste (interest), employment, income, social status, price, and habits (ethnicity, customs, culture, religion). Consumer behavior in the district of Batang against substitutes to meet the needs and desires do not change the configuration (the sort order) needs of human life. What has changed is the element (element) of goods is in it.Â Key words: Behavior patterns, consumer behavior, need, maslahah, iso-maslahah.Â